Effect of degassing addition on the corrosion of nickel aluminum bronze - Kavin, J.; Azam, M.; Ahmad, A. H.; Shayfull, Z.; Mohd Rashidi, Maarof (AIP Publishing, 2018)
The effect of degassing agent addition on the corrosion of Nickel Aluminum Bronze was investigated. The complex relationship between the degassing effects on corrosion behaviour of the alloy was obtained by using weight loss method. This experiment describes the corrosion characterization of Nickel Aluminum Bronze which was interpret after amount of time set. With this method, the differences of weight due to corrosion rate were clearly measured and evidenced. The results show alloy corrosion is directly affected by the percentage of degassing agent added in molten Nickel Aluminum Bronze alloy. Higher degassing addition on the Nickel Aluminum Bronze decreased the corrosion rate.